ENVIRONMENTAL POLICY IN TURKEY AND INTERNATIONAL ENVIRONMENTAL AGREEMENTS - Bahar TÜRK (Fırat University, 2019)
The endeavor of mankind to sustain life, the inevitable interaction between man and environment, the point that the concept of environment is today, the concept of environment require to be addressed in international dimensions as well as in the national dimension. In addition, many protocols, arrangements and contracts concerning the environment at the international level clearly demonstrate the importance of this issue. Therefore, the steps to be taken in the national sense are also very important for the creation of a globally meaningful whole. The means to be used/used in creating environmental awareness and the environmental policies that are carried out effectively are the main building blocks to provide this integrity. The Stockholm Conference, organized by the United Nations on June 5, 1972, is considered to be the turning point of international policies on environmental issues. This conference, which was attended by the participation of 113 countries, including our country, has proved that it is necessary to seek a global solution to environmental problems as well as to establish a generally accepted platform for environmental issues. It was also recognized as the World Environment Day on June 5th with the declaration issued as the conclusion of the conference. The Environment Day is dedicated to carrying out an important function, such as increasing environmental protection activities and increasing environmental awareness to improve environmental quality. The environmental conception that starts with the Stockholm Conference has become an increasingly important and more comprehensive topic in our country and around the world. For this reason, examined first in Turkey, followed by international environmental practices, legislation and contracts in study.